Optimization of Based Academic Management Information Systems E-Learning in Improving the Quality of Learning in State Madrasah Aliyah 1 and 2 Bandung City - Mayasari, Annisa; Ruswandi, Uus; Supiana, Supiana; Hasbiyallah, Hasbiyallah (International Journal of Education and Digital Learning (IJEDL), 2024)
This research is motivated by the existence and role of information technology which has brought a new era in the development of education but has not been matched by an increase in human resources. These conditions encourage changes in various aspects to accelerate improvements to achieve the goal of quality education. The aim of this research is to identify planning, organizing, implementing, monitoring, supporting and inhibiting factors as well as the impact of an e-learning based academic management information system in improving the quality of learning in MAN 1 and 2 Bandung City. The approach to this research uses a qualitative approach. The research method used in this research is the case study method. The impact of an e-learning based Academic Management Information System in improving the quality of learning in MAN 1 and 2 Bandung City, namely with attractive slide displays (eye- catching), good learning methods, teachers and students can carry out the learning process in a serious and fun way. This is acknowledged by students, that with the implementation of an e-learning based academic management information system in improving the quality of learning in schools, the learning process becomes varied and not boring.